Adjustments to cash build-up when retaining dividends in the FCFE valuation - Silva, João Marques (2017)
Valuation based on DCF (Discounted Cash Flow) has been the dominant valuation procedure during the last decades. In spite of this dominance, enterprise valuation using the discounted FCF (Free Cash Flow) model has some practical drawbacks, since there is often some confusion on how to effectively use it. Commonly, the valuation procedures start by estimating future FCF figures from historical data, such as mean FCF, growth and retention ratio, alongside many other variables. These FCF forecasts are discounted at the cost of equity (FCFE – FCF to Equit1y) or the Weighted Average Cost of Capital WACC (FCFF – FCF to Firm). Implicit in the above mentioned valuation procedures is the expectation that the company puts the free cash that it is generating to good use, yielding a value capable of rewarding appropriately the level of risk inherent in the way it used. In other words, the enterprise is not supposed to just shelve the cash generated or alternatively, investing it in bank accounts with returns below the equilibrium returns available in the market for the same level of risk. However, most of the times, the return rate isn’t the same as initially expected, being either higher or lower than the market’s expectation, with significant changes to the cash build-up on the company. This paper analyzes such changes and introduces a correction factor to the cash build-up.